The effect of PEG on callus growth of Tomato plants Lycopersicon escolentum mill - Ashwaq A.; Zahra N. Al Hattab; Wajida K. Al Qaudhy; Ekhlas Al Kaaby; Sammer F. Al Tahhan; Jenan A. Al Ani (Journal of Madenat Alelem University College, 2015)
Tissue culture technique was used to induce calli from shoot tips of tomato (Super Regina CV.) plants. Sterilized seeds were grown in test tubes on MS medium under sterilized condition in the growth room. Four weeks later, shoot tips were excised and cultured on MS medium supplemented with 0.6 mg/lIBA and 1mg/lBA to induce callus. The produced calli were transferred to MS medium supplemented with 0, 20, 40, 60 gm/l Polyethylene Glycol (PEG-6000). The results showed that there is negative correlation between calli fresh weight and PEG concentration. The highest average fresh weight,was for the calli that were grown in the control treatment and it was 0.35 g. While the lowest average fresh weight, was for the calli that were grown on 60 g/l PEG treatment and it was 0.19 g. Statistical analysis showed significant differences between the treatments and the control at (P=0.05).Reduction in dry weight to half was detected in the presenceof PEG of 20 and 60 g/l and it was 0.02 g for both 20 and 60 g/l PEG treatments.Moreover the results showed significant differences among the different treatments in the proline content of the calli. The amount of proline increased as the PEG concentration increased. The 60 and 40 g/l PEG treatments surpassed the other treatments in the proline content which was 3.89 and 5.61 µg / g of callus dry weight compared with 1.78 µg / g for the control. High proline concentration in the tissue indicates the ability of the tissue to use this mechanism to tolerate drought stress.